Atomic force microscopy studies of the KF (100) surface: formation of water-rich surface phases in moist N,N-dimethylformamide. - Macfie, G; Wilkins, S; Compton, R (2002)
A water rich surface phase is observed in the system KF-DMF-H2O by atomic force microscopy; the effects on surface morphology and likely implications for halogen exchange reactions using KF are discussed.